Color tunability of organic light emitting devices through Singlet oxygen Color tunability of organic light emitting devices through singlet oxygen exposure of chemical dopants - Ramjattan, Sanya Tamira (Tufts Archival Research Center, 2005)
Display technologies are rapidly developing to match consumer needs and manufacturers are becoming more interested in organic light emitting devices (OLEDs) as they are promising candidates for flexible displays and light-weight, transparent devices. This research involved the fabrication and optimization of novel OLEDs incorporating doped photo-emissive polyfluorenes, with the specific goal of achieving patternable devices for economic manufacture. The experimental methods employed are less energy intensive and more amenable to flexible applications than those for most inorganic LEDs. Devices synthesized with a blue-emitting polyfluorene and doped with green, amber and red emitting acenes have been characterized. The electroluminescent stability and color tunability of dopant endoperoxides have also been investigated. Doping was found to increase external quantum efficiency by two orders of magnitude; the trend in efficiency mirrored the degree of overlap between dopant absorption and host emission. Oxidation of acenes to form the endoperoxide produced electroluminescent spectra which exhibited different color and stability characteristics from un-oxidized devices. Evidence of the polyfluorene host was present in peroxide spectra but not in doped device spectra, indicating that oxidation successfully deactivated dopants and achieved color tunability. The exception was pentacene peroxide devices which became more stable after treatment and demonstrated high efficiency but no change in color.